Resistencia mecánica del suelo a la penetración de raíces y forma de la raíz reservante de la batata a partir del descriptor de Huamán - Pérez, Maiby (2016)
Soil mechanical resistance to root penetration and shape of the reserve root of sweet potato from the Huaman descriptor. A study was carried out in order to evaluate the influence of mechanical resistance to root penetration (PR), in a soil affected by tillage and seeding distance, on the shape of the reserve root of a sweet potato crop (Ipomoea batatas (L.) Lamb). Experimental design was based on a strip plot arrangement, where big lots were assigned to tillage systems (TS) and seeding density (SD) to strips. The TS consisted of: 1) deep vertical tillage with chisel (CT); 2) tillage with disc plow (DT); 3) conventional tillage with 3 harrow passes (CoT); and 4) minimum tillage with one harrow pass (MT). With 4 tillage working depths of 18, 23, 12 y 7 cm, respectively. The SD were of 0.25 cm (D1) and 0.15 cm (D2) on the crop row. RP average was higher at deeper soil layers for MT treatments (5-15, 15-25 cm) by 44 and 37%, with respect to that observed at same soil layers in the rest of tillage systems. There was scant difference between medium and deep tillage systems (CoT, CT, DT) for PR. The shape of the reserve root was variable, a rounded shape found mostly in MT treatments, contrary to that expected considering the greater restriction to longitudinal root growth on soils with higher strength under MT. This partly explained by the non-restrictive values to soil root penetration (< 2 MPa) found for the different treatments.